2021
DOI: 10.1371/journal.pone.0251048
|View full text |Cite
|
Sign up to set email alerts
|

Acute kidney injury: Incidence, risk factors, and outcomes in severe COVID-19 patients

Abstract: Background COVID-19 is a multisystemic disorder that frequently causes acute kidney injury (AKI). However, the precise clinical and biochemical variables associated with AKI progression in patients with severe COVID-19 remain unclear. Methods We performed a retrospective study on 278 hospitalized patients who were admitted to the ward and intensive care unit (ICU) with COVID-19 between March 2020 and June 2020, at the University Hospital, São Paulo, Brazil. Patients aged ≥ 18 years with COVID-19 confirmed on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
27
3
8

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(45 citation statements)
references
References 53 publications
7
27
3
8
Order By: Relevance
“…We identified risk factors for the development of CA-AKI, is likely to be multifactorial, with cardiovascular comorbidity and predisposing factors as important contributors [ 27 ] including comorbidities such as diabetes, hypertension, CKD and COPD, and debilitating chronic diseases that have been universally associated with a worse evolution of COVID 19. In addition, we also identified that the severity of COVID and markers linked to inflammation, which is consistent with the pathophysiological mechanisms described in its pathology, where high inflammatory activity plays a preponderant role in kidney injury [ 34 ], evident in high levels of leukocytes (> 12 109/L) and ferritin (> 500 ng/mL), similar to ferritin levels (798 ng/mL) previously described by the Northwell COVID-19 Research Consortium [ 22 ] and similar leukocytes than the Brazilian cohort [ 20 ] cohort.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…We identified risk factors for the development of CA-AKI, is likely to be multifactorial, with cardiovascular comorbidity and predisposing factors as important contributors [ 27 ] including comorbidities such as diabetes, hypertension, CKD and COPD, and debilitating chronic diseases that have been universally associated with a worse evolution of COVID 19. In addition, we also identified that the severity of COVID and markers linked to inflammation, which is consistent with the pathophysiological mechanisms described in its pathology, where high inflammatory activity plays a preponderant role in kidney injury [ 34 ], evident in high levels of leukocytes (> 12 109/L) and ferritin (> 500 ng/mL), similar to ferritin levels (798 ng/mL) previously described by the Northwell COVID-19 Research Consortium [ 22 ] and similar leukocytes than the Brazilian cohort [ 20 ] cohort.…”
Section: Discussionsupporting
confidence: 83%
“…high inflammatory activity plays a preponderant role in kidney injury [34], evident in high levels of leukocytes (> 12 109/L) and ferritin (> 500 ng/mL), similar to ferritin levels (798 ng/ mL) previously described by the Northwell COVID-19 Research Consortium [22] and similar leukocytes than the Brazilian cohort [20] cohort.…”
Section: Plos Onesupporting
confidence: 76%
See 1 more Smart Citation
“…As mentioned above, we found that a long-term therapeutic dose of HCQ for LN may disrupt autophagy and promote senescence in PTECs to increase the susceptibility to AKI. Recently, HCQ or CQ use in COVID-19 patients was also emphasized that these drugs may worsen AKI by inhibiting autophagy [ 47 49 ]. A previous study by Tang et al [ 50 ] found that short-term HCQ therapy attenuated I/R-induced AKI, although the autophagy pathway was also inhibited.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the high tropism of virus at tissues as heart, kidney and blood vessels has been observed in the pathophysiology of COVID-19: acute heart failure, dysrhythmia, myocarditis, thromboembolism events (arterial and venal) [7]; acute renal failure [12,13]; neurological damage such as impaired consciousness, stroke; liver dysfunction; blood dysfunction (i.e. metabolic acidosis) [6]; thrombosis [14]; septic shock and multiple organ failure [15,16].…”
Section: Covid-19 and Sars-cov-2 Pathophysiologymentioning
confidence: 99%